Slip Length Enhancement in Nanofluidic Flow using Nanotextured Superhydrophobic Surfaces. Issue 17 (28th June 2016) - Heverhagen, Jonas; Tasinkevych, Mykola; Rahman, Atikur; Black, Charles T.; Checco, Antonio
Abstract : The development of highly efficient nanofluidic devices necessitates means for enhancing and controlling fluid transport under confinement. Here, it is shown experimentally that significant interfacial drag reduction in nanoscale channels can be obtained with hydrophobic arrays of conical textures tapering to a radius of less than 10 nanometers at their tip. This geometry maximizes interfacial slippage by trapping a highly resilient air layer at the solid/liquid interface. Further, it is revealed that the composite liquid/solid‐air interface bears an electrostatic charge density comparable to that of a flat hydrophobic solid. Altogether these properties render the nanotextured surfaces highly attractive for efficient nanofluidic transport both in pressure‐driven and electroosmotic flow. Abstract : Hydrophobic arrays of sharp conical nanotextures significantly enhance flow in slit‐like nanochannels. The texture traps a highly pressure‐resilient air layer which increases liquid slippage. Furthermore, negative charge accumulation at the liquid/air interface enables efficient electroosmotic flow.